Odpowiedzi

Najlepsza Odpowiedź!
  • Użytkownik Zadane
2009-10-15T19:55:28+02:00
-(6a+4)/2-(9a-3)/3=[-3(6a+4)]/6 -[2(9a-3)]/6=[-3(6a+4)-2(9a-3)]/6=[-18a-12-18a+6]/6=[-36a-6]/6=[6(-6a-1)]/6=-6a-1
1 5 1
2009-10-15T19:55:37+02:00
-(6a+4)/2-(9a-3)/3= -(3a+4)-(3a-1)= -6a-3
2009-10-15T19:58:59+02:00
-(6a+4) (9a-3) -3(6a+4) 2(9a-3)
______ - _______= ___________ - ____________=
2 3 6 6

-(18a+12)-(18a-6) -18a-12-18a+6 -36a-6
=_________________ = _______________ = ________________
6 6 6


(-36a-6)/6=0 *6
-36a-6=0
-36a=6
a=-6/36=-1/6